Photocatalytical activity of amorphous hydrogenated TiO2 obtained by pulsed laser ablation in liquid. (February 2016) - Zimbone, M.; Cacciato, G.; Buccheri, M.A.; Sanz, R.; Piluso, N.; Reitano, R.; La Via, F.; Grimaldi, M.G.; Privitera, V.
Abstract: This work focuses on the photo-catalytic activity of TiO2 nanoparticles produced by an alternative, industrially compatible and environmentally friendly technique such as laser ablation in liquids. Amorphous and highly hydroxylated TiO2 nanoparticles were synthesized by using the first harmonic of a Nd:Yag laser. Despite their amorphous phase, the nanoparticles showed a photocatalytic activity comparable to that of crystalline TiO2 in the degradation of Methylene Blue dye. This unexpected high rate is discussed taking into account the amount of hydroxyl groups and the presence of amorphous phase. Furthermore, a possible mechanism to achieve this high activity is pointed out.